Inferring origin of mercury inclusions in quartz by multifractal analysis - Shibata, T.; Maruoka, T.; Echigo, T. (Nonlinear processes in geophysics, 2015)
In order to refine our understanding of how fluid inclusions were trapped in the host minerals, we non-destructively observed mercury inclusions (liquid Hg0) in quartz samples using X-ray computed tomography (CT) technique. The X-ray CT apparatus can observe internal structures of the samples and give cross-sectional images from the transmission of the X-rays through the samples. From the cross-sectional images, we obtained three-dimensional spatial distributions of mercury inclusions, and quantitatively analyzed them using fractal and multifractal methods. Although the samples were from different geological settings, the resultant fractal dimensions were 1.70 and 1.71 for the San Benito and Itomuka samples, respectively. The fractal dimensions were also close to those predicted by diffusion-limited aggregation models and percolation theory, which are controlled by the irreversible kinetics. Given the fractal dimension and its implied mechanism, we conclude that the mercury-bearing fluids were not primary fluid inclusions, but migrated into the pre-existing cracks of quartz crystals by diffusion processes.